Resolution of the X All-Russian scientific and practical conference «Strategy for controlling antibiotic resistance in hospital settings» - Agibalova M.N.; Bozhkova S.A.; Vorykhanov A.V.; Gaboyan Ya.S.; Goryunov S.V.; Gusarov V.G.; Zamyatin M.N.; Kamyshova D.A.; Kozlov R.S.; Kuzmenkov A.Yu.; Kulabukhov V.V.; Ni O.G.; et al. (Клиническая микробиология и антимикробная химиотерапия)
The aim of the resolution was to develop a coordinated expert position on the problematic issues of organizing a strategy for controlling antibiotic resistance and the rational use of antibacterial drugs. Antibiotic resistance (AMR) is one of the most global threats to human health. The rapid spread of microorganisms resistant to antimicrobial drugs (AMP) threatens the effectiveness of patient treatment, leads to an increase in complications, an increase in the duration of hospitalization, and colossal economic losses. Despite the efforts being made, the level of resistance of key bacterial pathogens to critically important AMPs remains high, and the possibilities for treating severe infections are rapidly declining. Successful counteraction to this threat requires a comprehensive, intersystemic approach that unites public health, veterinary medicine, environmental protection, and agriculture. However, the effectiveness of any AMR control strategies directly depends on solving key systemic problems within the healthcare sector. The conference addressed important issues in this area: implementation of priority areas of state policy to prevent the spread of AMR in the Russian Federation; availability of microbiological diagnostics and effective antimicrobial therapy; the role of digital technologies in monitoring AMR; programs for managing the prescription of AMR and containing the spread of antibiotic resistance; practical implementation of the concept of targeted antimicrobial therapy.